2022
DOI: 10.1107/s160057672200766x
|View full text |Cite
|
Sign up to set email alerts
|

HTD2: a single-crystal X-ray diffractometer for combined high-pressure/low-temperature experiments at laboratory scale

Abstract: High-pressure (HP) X-ray diffraction experiments at low temperature (LT) require dedicated instruments as well as non-standard sample environments and measuring strategies. This is especially true when helium cryogenic temperatures below 80 K are targeted. Furthermore, only experiments on single-crystalline samples provide the prerequisites to study subtle structural changes in the p–T phase diagram under extreme LT and HP conditions in greater detail. Due to special hardware requirements, such measurements ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 95 publications
(108 reference statements)
1
10
0
Order By: Relevance
“…Two different setups were employed to collect the XRD data in this paper: an experiment at 100(2) K was performed on a BRUKER Smart-Apex diffractometer featuring a D8 goniometer, an APEX II CCD detector, an INCOATEC AgK α microfocus sealed-tube as an X-ray source (λ = 0.56087 Å), and a standard OXFORD open-flow N 2 cooler (diffractometer 1) . Experiments at temperatures from RT down to sub-nitrogen cryogenic temperatures relied on a HUBER four-circle Eulerian cradle goniometer equipped with a DECTRIS Pilatus3R CdTe 300K pixel detector, an INCOATEC AgK α microfocus sealed-tube X-ray source (λ = 0.56087 Å), and an ARS closed-cycle helium cryocooler with an outer and inner beryllium vacuum and radiation shield (diffractometer 2) . Data collection at different temperatures was performed in direct sequence without sample reorientation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two different setups were employed to collect the XRD data in this paper: an experiment at 100(2) K was performed on a BRUKER Smart-Apex diffractometer featuring a D8 goniometer, an APEX II CCD detector, an INCOATEC AgK α microfocus sealed-tube as an X-ray source (λ = 0.56087 Å), and a standard OXFORD open-flow N 2 cooler (diffractometer 1) . Experiments at temperatures from RT down to sub-nitrogen cryogenic temperatures relied on a HUBER four-circle Eulerian cradle goniometer equipped with a DECTRIS Pilatus3R CdTe 300K pixel detector, an INCOATEC AgK α microfocus sealed-tube X-ray source (λ = 0.56087 Å), and an ARS closed-cycle helium cryocooler with an outer and inner beryllium vacuum and radiation shield (diffractometer 2) . Data collection at different temperatures was performed in direct sequence without sample reorientation.…”
Section: Methodsmentioning
confidence: 99%
“…13 Experiments at temperatures from RT down to sub-nitrogen cryogenic temperatures relied on a HUBER four-circle Eulerian cradle goniometer equipped with a DECTRIS Pilatus3R CdTe 300K pixel detector, an INCOATEC AgK α microfocus sealed-tube X-ray source (λ = 0.56087 Å), and an ARS closed-cycle helium cryocooler with an outer and inner beryllium vacuum and radiation shield (diffractometer 2). 14 Data collection at different temperatures was performed in direct sequence without sample reorientation. Recorded Bragg intensities were evaluated using the APEX2 12 (diffractometer 1) or the EVAL14 integration programs 15,16 (diffractometer 2) and subjected to scaling and absorption corrections using the program SADABS.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The presence of a Peierls-type structurally distorted low-temperature phase in the transition-metal carbide Sc 3 CoC 4 has been observed in several earlier investigations [46][47][48][49][50][51][52]. It could be shown that the structural changes between high-temperature (HT) phase (space group Immm, no.…”
Section: The Peierls-type Structural Distortion In Sc3coc4mentioning
confidence: 73%
“…Additional laboratory-scale XRD experiments in the temperature range between 10 K and 300 K were performed employing a Huber four-circle Eulerian cradle goniometer fitted with an Incoatec AgK α microfocus sealedtube x-ray source (λ = 0.56087 Å), a Dectris PILATUS3 R CdTe 300K hybrid-pixel detector and an Advanced Research Systems closed-cycle helium cryocooler with domed beryllium vacuum and radiation shields (subsequently referred to as "laboratory-scale instrumental setup 2"; see Ref. 52 for a detailed description). The collected XRD data sets were processed using the program eval14 [68][69][70] to determine unit cell parameters and reflection intensities corresponding to the orthorhombic and monoclinic unit cells of HT-phase and LT-phase structural models.…”
Section: X-ray Diffractionmentioning
confidence: 99%
See 1 more Smart Citation